Combustible and Electronic Cigarette Use and Insufficient Sleep among U.S. High School Students - Merianos, Ashley L. (Prev Med, 2021)
The study aimed to investigate the relationships between current exclusive e-cigarette use, exclusive combustible cigarette smoking, and dual use of e-cigarettes and combustible cigarettes, and insufficient sleep among U.S. adolescents. We conducted a secondary data analysis of the 2017 Youth Risk Behavior Survey including 11,296 U.S. high school students. Current (past 30-day) tobacco use groups included exclusive e-cigarette users, exclusive combustible cigarette smokers, and dual-product users. We performed weighted unadjusted and adjusted logistic regression analyses. Insufficient sleep was defined as <8 hours/night and <7 hours/night. Overall, 73.4% of adolescents reported insufficient sleep <8 hours/night. Compared with non-tobacco users, exclusive e-cigarette users were more likely to report insufficient sleep <8 hours/night (odds ratio [OR]=1.55, 95%CI=1.12–2.14; adjusted OR [aOR]=1.57, 95%CI=1.01–2.43) and <7 hours/night (OR=1.55, 95%CI=1.19–2.01; aOR=1.61, 95%CI=1.16–2.24). Dual-product users were at increased odds to report insufficient sleep <8 hours/night (OR=3.15, 95%CI=1.87–5.32) and <7 hours/night (OR=2.64, 95%CI=1.87–3.72; aOR=1.73, 95%CI=1.14–2.62) than non-tobacco users. Exclusive combustible cigarette smokers were less likely to report insufficient sleep <8 hours/night (aOR=0.49, 95%CI=0.29–0.84) than non-tobacco users, but no differences were found based on insufficient sleep <7 hours/night. When comparing current use groups, exclusive e-cigarette users were at 3.20 increased odds (95%CI=1.65–6.22) and dual-product users were at 3.26 increased odds (95%CI=1.51–7.03) to report insufficient sleep <8 hours/night when compared with exclusive combustible cigarette smokers after covariate adjustment. Dual-product users were 1.89 times more likely (95%CI=1.01–3.51) to report insufficient sleep <7 hours/night when compared with exclusive combustible cigarette smokers. School-based prevention efforts for tobacco use may promote sufficient sleep in youth.